The Impact Of The Pandemic And The Implementation Of Sales Strategies On People's Buying Interest In The New Normal - Shelren (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
This research was motivated by the decline in people's buying interest during the pandemic which was marked by a decline in sales. This study aims to determine the sales strategy for purchasing interest from the customers at Rezeki Baru which is a grocery store located in Batang Kuis, Nort Sumatera. The research was conducted in September 2022 through observing the customer who has been purchased things in Rezeki Baru. The data collection technique in the study is provided by questionnaire to consumers at Rezeki Baru and made observations. The analytical technique used in this study is quantitative using a questionnaire. The population used is consumers at Rezeki Baru. The sampling technique is simple random sampling. Meanwhile, to analyze the data, a validity test using Pearson product was used, and Croncbach's Alpha as a reliability test. For prerequisite analysis testing, normality testing, multicollinearity test, and heteroskedasticity test are used. Then in testing against hypotheses, partial t test, F test and determination test are used. The results of this study were obtained based on the calculation of the t test with a coefficient of sig value. from the Impact of the Pandemic on The Purchase Interest generates a value of 0.002 < 0.05 and the sig. value of the Sales Strategy on the Purchase Interest produces a value of 0.000 < 0.05 which means that the higher the level of pandemic impact, the higher the value of the effect on the Purchase Interest. Where it can be seen that the pandemic has greatly influenced the decline in people's purchase interest in Rezeki Baru.